Analysis of Factors Affecting Self Care in Kusta Patients in Daha Husada Kediri Hospital - Hadi Santoso; Nurdina Nurdina; Nurwijayanti Nurwijayanti (Journal for Quality in Public Health, 2019)
Leprosy is a disease that can lead to physical disability and psychological disorders in leprosy patients who can be significantly reduced by self care. Several factors that can affect self care in leprosy patients include the degree of disability, stigma, family support and self-acceptance. This study aims to analyze the factors that influence self care in leprosy patients at Daha Husada Kediri Hospital. The research design used in this study is analytic with a cross sectional approach. The number of samples in this study is 116 respondents who meet the inclusion criteria and are taken by the rendom sampling technique. The independent variable in this study is the degree of disability, stigma, family support and self-acceptance while the dependent variable is self care. Data analysis using Pearson Correlation and Beta Coefficient statistical tests The results showed that the majority of leprosy patients had a disability level of 1 (62.9%), moderate stigma (58.6%), high family support (52.6%) and acceptance moderate self (53.4%), The results of the Pearson correlation statistical test showed that family support p 0,000 Pearson correlation 0,483 and self-acceptance p 0,000 Pearson correlation 0,584 were meaningful and from the results of the regression coefficients the Beta Coefficient showed that self-acceptance was the most powerful factor with self care in leprosy patients at Daha Husada Kediri Hospital. Daha Husada Kediri Hospital is expected to be able to further improve health service efforts to change the negative stigma in the community by socializing leprosy